2019
DOI: 10.1186/s12859-019-2974-3
|View full text |Cite
|
Sign up to set email alerts
|

miRFA: an automated pipeline for microRNA functional analysis with correlation support from TCGA and TCPA expression data in pancreatic cancer

Abstract: Background MicroRNAs (miRNAs) are small RNAs that regulate gene expression at a post-transcriptional level and are emerging as potentially important biomarkers for various disease states, including pancreatic cancer. In silico-based functional analysis of miRNAs usually consists of miRNA target prediction and functional enrichment analysis of miRNA targets. Since miRNA target prediction methods generate a large number of false positive target genes, further validation to narrow down interesting ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…MiRComb [ 13 ] conducts a miRNA-mRNA expression analysis followed by miRNA target prediction on the negatively correlated mRNA targets. miRFA [ 14 ] considers both the negatively and positively correlated using TCGA data. miTALOS [ 15 , 16 ] additionally provides a tissue-specific filtering of the targets.…”
Section: Introductionmentioning
confidence: 99%
“…MiRComb [ 13 ] conducts a miRNA-mRNA expression analysis followed by miRNA target prediction on the negatively correlated mRNA targets. miRFA [ 14 ] considers both the negatively and positively correlated using TCGA data. miTALOS [ 15 , 16 ] additionally provides a tissue-specific filtering of the targets.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, an analysis of the main components (PCA) was performed. Later, the target genes of the selected miRNAs were determined using the R miRFA pipeline [ 28 ], which is supported by data from the DIANA-TarBase v7, DIANA-microT-CDS and TargetScan v7.1 databases. Additionally, UniProt and Gene Ontology databases have been used to search for terms associated with the trabecular meshwork functions and the glaucoma pathology [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Apparently Apart from this, high-dose ATO (5 mg/kg), low-dose ATO (1 mg / kg) and saline were used as the control group for local injection of subcutaneous transplanted tumor [19]. For the reason that we put [24]. However, some studies have shown that increased levels of miRNA-885-5p in tissues or body fluids can be used as diagnostic markers for tumors and short survival period.…”
Section: Validation Of Prognostic Values Of Mir-885-5p and Mtpn In Ccamentioning
confidence: 99%